STUDY ON EFFECT OF CHENOPODIUM QUINOA ON GROWTH PERFORMANCE, CARCASS COMPOSITION AND ANTIOXIDANT ACTIVITY OF OREOCHROMIS NILOTICUS AND CYPRINUS CARPIO - Syed Makhdoom Hussain; Misbah Noor; Fatima Khurram; Abdullah Ijaz Hussain; Muhammad Zubair-ul-Hassan Arsalan; Nisar Ahmad; Danish Riaz (Journal of Animal and Plant Sciences, 2024)
Plant-based protein sources are suitable and profitable for aquaculture. Chenopodium quinoa is one of the pseudo-cereal plants and promising source of protein. A 60-day feeding experiment was designed to check the impacts of C. quinoa seed meal (CQSM) on growth indices, carcass composition and antioxidant activity of Oreochromis niloticus and Cyprinus carpio. Six test diets as I, II, III, IV, V and VI were formed by using CQSM as replacement of fishmeal (FM) at 0%, 10%, 20%, 30%, 40% and 50%, respectively. Triplicate tanks having 15 juveniles in each were used and juveniles were fed at a diet equivalent to 5% of their live wet weight. Digestibility was measured with the help of feces. In O. niloticus and C. carpio, maximum results for weight gain (13.65g), (14.12g), feed conversion ratio (FCR) (0.98), (0.92), weight gain% (168.80), (199.15), and specific growth rate (SGR) (1.63), (1.21), respectively, were seen at level-III (20%) replacement of FM with C. quinoa seed meal based diet. For nutrient digestibility, best results in O. niloticus and C. carpio were also noticed at 20% replacement of FM with CQSM as crude protein (CP) (68.59), (66.30), crude fat (CF) (65.82) (65.65) and gross energy (GE) (72.36), (65.60), respectively. The antioxidant activity was maximum: 6.56 for O. niloticus and 7.13 for C. carpio at 20% replacement of FM. The findings indicated that the substitution of FM with CQSM up to 20% has a positive effect on fish growth, carcass composition, antioxidant activity and nutrient digestibility.
Keywords: Quinoa seed meal; Pseudocereal plants; Fishmeal; Growth performance; Antioxidant activity